2021
DOI: 10.1186/s13731-021-00165-5
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of micro and small enterprise growth in North Wollo and Waghimira Zone selected towns

Abstract: This study aims to investigate the socioeconomic determinant factors that affect the growth of micro and small enterprises (MSEs) in North Wollo and Waghimira Zone selected towns. In this study, a cross-sectional research design with both descriptive and explanatory research design has been employed, and 303 owners of enterprises have participated. The towns were selected purposely, and the respondents were also selected by using a simple random sampling technique. The data were analyzed by using STATA v-14 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…Hence, SMEs can unlock their learning potential in new halal product development and subsequently, achieve economic sustainability. Therefore, SMEs offer the best solutions to the country’s gross domestic development, reduction of unemployment, and creating smooth economic environment (Kassa, 2021 ). Furthermore, Kostis ( 2021 ) stated that SMEs and society are not ready to accept policy change, which would result in policy failure as well as ineffective policy responses, innovation outcomes, and economic development, affecting the sustainability of the overall economic system.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, SMEs can unlock their learning potential in new halal product development and subsequently, achieve economic sustainability. Therefore, SMEs offer the best solutions to the country’s gross domestic development, reduction of unemployment, and creating smooth economic environment (Kassa, 2021 ). Furthermore, Kostis ( 2021 ) stated that SMEs and society are not ready to accept policy change, which would result in policy failure as well as ineffective policy responses, innovation outcomes, and economic development, affecting the sustainability of the overall economic system.…”
Section: Discussionmentioning
confidence: 99%
“…But, they concluded that marital status has an insignificant relationship with economic achievement for women. Kassa (2021) conducted a cross-sectional study to investigate the socio-economic determinant factors that affect the growth of micro and small enterprises (MSEs) in Ethiopia's North Wollo and Waghimira Zone. The finding of the study revealed that the age of the owner, access to finance, family business background and interest rate most likely affect the growth of the enterprises with a statistically significant level.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Eshetu and Zeleke (2008) find out that adequacy of finance, level of education, level of managerial skills, level of technical skills, and ability to convert part of their profit to investment are factors affecting the survival of MSE. Alene (2020), Meressa (2020), Mamo (2022) and Kassa (2021) added that access to business training, tax, land ownership, age of the owner, access to finance, family business background, and interest rate most likely affect the growth of the enterprises affect the growth of the enterprises.…”
Section: Empirical Studiesmentioning
confidence: 99%